A(x - x₁)(x - x₂) = 0
a=5, x₁=-3, x₂ = 3
so:
5(x-(-3))(x-3)=0
5(x+3)(x-3)=0
5(x²-9) = 0
5x² - 45 = 0 ← answer
Answer:
![\displaystyle 125^i](https://tex.z-dn.net/?f=%5Cdisplaystyle%20125%5Ei)
Step-by-step explanation:
<u>Extended Information </u><u>on</u><u> </u><u>the</u><u> Complex Number System</u>
![\displaystyle \sqrt{-1} = i \\ -1 = i^2 \\ -i = i^3 \\ 1 = i^4\:[all\:multiples\:of\:four]](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csqrt%7B-1%7D%20%3D%20i%20%5C%5C%20-1%20%3D%20i%5E2%20%5C%5C%20-i%20%3D%20i%5E3%20%5C%5C%201%20%3D%20i%5E4%5C%3A%5Ball%5C%3Amultiples%5C%3Aof%5C%3Afour%5D)
I am joyous to assist you at any time.
All work is shown above. ↑
Answer
False
Step-by-step explanation:
Answer: 16.13
Step-by-step explanation: 40 divided by $2.48